Politicshock : Trump, Modi, brexit & the prospect for liberal democracy - Desai, Meghnad (New Delhi, 2017)
Recent events around the world have shaken old certainties. Questions are being asked about the survival of the Liberal Order, which has been dominant for over fifty years. The election of Donald Trump and the Brexit vote have alarmed many commentators. Across Europe too there have been developments?the emergence of fringe parties of the left and right in France, Germany, Spain, Italy and Greece?which have disturbed the liberal thought. In India, the arrival of Narendra Modi at the head of the ?Hindu nationalist? Bharatiya Janata Party (BJP) in 2014 had raised fear similar to those in Trump?s case. In this perceptive account, Meghnad Desai opens up the debate beyond the West and looks at parallels between Prime Minister Narendra Modi and US President Donald Trump as two outsiders who broke through the barriers to reach the top. He analyses Asia?s challenge to Western hegemony and asks if the conventional wisdom about the hegemony of free trade liberalism needs re-examination. He peers into the future to look at the greatest challenge facing the world today: Will the Liberal Order survive, collapse or mutate? Is the world at a cusp? Is history?the old saga of blood, sweat and tears?about to resume its course? Politicshock analyses Trump and Modi and other outsiders who have come to the fore not as freaks but as results of systematic forces?economic, social, political and cultural?who will now shape the critical destiny of the time that we live in.
Keywords: India